The Toxicity of Silver Nanoparticles Depends on Their Uptake by Cells and Thus on Their Surface Chemistry. (17th July 2013) - Caballero‐Díaz, Encarnación; Pfeiffer, Christian; Kastl, Lena; Rivera‐Gil, Pilar; Simonet, Bartolome; Valcárcel, Miguel; Jiménez‐Lamana, Javier; Laborda, Francisco; Parak, Wolfgang J.
<x xml:space="preserve">Abstract</x> A set of three types of silver nanoparticles (Ag NPs) are prepared, which have the same Ag cores, but different surface chemistry. Ag cores are stabilized with mercaptoundecanoic acid (MUA) or with a polymer shell [poly(isobutylene‐alt‐maleic anhydride) (PMA)]. In order to reduce cellular uptake, the polymer‐coated Ag NPs are additionally modified with polyethylene glycol (PEG). Corrosion (oxidation) of the NPs is quantified and their colloidal stability is investigated. MUA‐coated NPs have a much lower colloidal stability than PMA‐coated NPs and are largely agglomerated. All Ag NPs corrode faster in an acidic environment and thus more Ag(I) ions are released inside endosomal/lysosomal compartments. PMA coating does not reduce leaching of Ag(I) ions compared with MUA coating. PEGylation reduces NP cellular uptake and also the toxicity. PMA‐coated NPs have reduced toxicity compared with MUA‐coated NPs. All studied Ag NPs were less toxic than free Ag(I) ions. All in all, the cytotoxicity of Ag NPs is correlated on their uptake by cells and agglomeration behavior.